N-Methyl-N-p-toluenesulfonylformamide: A Stable and Convenient N-formylating Agent - Khazaei, Ardeshir; Mehdipour, Ebrahim (Asian Journal of Chemistry, 2010)
N-Methyl-N-p-toluensulfonylformamide prepared by the reaction of N-methyl- p-toluenesulfonamide and formic acid, is demonstrated to be an effective N-formylating agent.